QTL Identification for Cooking and Eating Quality in indica Rice Using Multi-Parent Advanced Generation Intercross (MAGIC) Population - Ponce, Kimberly S.; Ye, Guoyou; Zhao, Xiangqian (Frontiers in Plant Science, 2018)
Association mapping using a multi-parent advanced generation intercross (MAGIC) population provides a promising tool in genetic dissection of rice cooking and eating quality (CEQ). In this study, QTLs were identified for ten physicochemical properties related to cooking and eating qualityCEQ using 508 F6 MAGIC lines. The whole population including and eight founder lines were genotyped with 6K Illumina Infinium HD Assay. All traits had high heritability estimates and shown showed a large genetic variation in the MAGIC population. Highly significant phenotypic correlations were present between traits. AC was significantly positively correlated with PKT, TV, FV, SBV, PKT and RT but significantly negative correlated with GC and BDV. Sixteen Seventeen QTLs were identified for all traits. GBSSI locus was hosted or closely to nine QTLs, qAC6, qGC6.1, qPKT6.1, qPKV6, qBDV6.1, qTV6.1, qFV6, qSBV6 and qRT6, suggesting that GBSSI impacts the overall cooking and eating qualityCEQ. Another locus closed to SSIIa, was anchored located at 6.99 Mb, affectsing five traits, GC, PKT, BDV, SBV and PT respectively. The identified QTLs showed multi-trait associations and revealed small to modest effects where the highest percentage of phenotypic variance explained was 17.18%. These QTLs are directly relevant and useful in breeding for cooking and eating qualityCEQ in indica rice. These results also confirmed that QTL mapping via association mapping using a MAGIC population is a powerful method in genetic analysis of complex traits.